2022
DOI: 10.1123/jsr.2021-0403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Therapy Interventions on Shoulder Pain and Musculoskeletal Risk Factors for Shoulder Pain in Competitive Swimmers: A Scoping Review

Abstract: Context: Shoulder pain is the main cause of missed or modified training in competitive swimmers. Exercise therapy can improve the outcomes, yet uncertainty exists regarding the characteristics of these interventions. Objectives: The primary aim was to describe the evidence base relating to the effectiveness of exercise therapy interventions on shoulder pain and shoulder musculoskeletal risk factors for shoulder pain in swimmers. The secondary aim was to identify gaps in the literature and provide recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In the present study, the inclusion of this risk factor as an inclusion criterion may have provided meaningful results in the study population, as altered scapular kinematics has also been shown to be a potential risk factor (Su et al, 2004). In contrast, there is no consensus on which of the therapeutic approaches developed to date to control the agonist-antagonist ratio is the most appropriate (Yoma et al, 2022). The present study did not obtain the expected results in terms of muscle strength and shoulder ROM.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, the inclusion of this risk factor as an inclusion criterion may have provided meaningful results in the study population, as altered scapular kinematics has also been shown to be a potential risk factor (Su et al, 2004). In contrast, there is no consensus on which of the therapeutic approaches developed to date to control the agonist-antagonist ratio is the most appropriate (Yoma et al, 2022). The present study did not obtain the expected results in terms of muscle strength and shoulder ROM.…”
Section: Discussionmentioning
confidence: 62%
“…Due to the impact of shoulder fatigue during swimming, it is possible that increased endurance of the posterior rotator cuff can enhance the stability of the humeral head in the glenoid. In turn, this may help mitigate the shoulders tendency for functional impingement, particularly during longer swimming sets 51 . Future studies should reappraise shoulder strength‐endurance, particularly the posterior shoulder test, to confirm its association with shoulder pain or injury, and whether any such association is causal or consequent.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, it is not known if altering any risk factor will decrease injury incidence. Preliminary evidence suggests exercise‐based programs in swimmers could reduce shoulder injury incidence 48,51,60,61 . Nevertheless, before meaningful conclusions can be drawn, subsequent investigations should include the following methodological improvements, larger samples, refined pain definitions, and longer monitoring periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations